Cerebrovascular Reserve Capacity as a Predictor of Postoperative Delirium: A Pilot Study - Bydén, Moa; Segernäs, Anna; Thulesius, Hans; Vanky, Farkas; Ahlgren, Eva; Skoog, Johan; Zachrisson, Helene (Frontiers in Surgery, 2021)
Introduction. Postoperative delirium is a common complication after cardiac surgery with cardiopulmonary bypass (CPB). Compromised regulation of the cerebral circulation may be a predisposing factor for delirium. However, the potential relationship between cerebrovascular reserve capacity and delirium is unknown. The aim of this study was to investigate if impaired cerebrovascular reserve capacity was associated with postoperative delirium. Methods. Forty-two patients scheduled for cardiac surgery with CPB were recruited consecutively. All patients underwent preoperative transcranial Doppler (TCD) ultrasound with calculation of breath-hold index (BHI). BHI < 0.69 indicated impaired cerebrovascular reserve capacity. In addition, patients were examined with preoperative neuropsychological tests such as MMSE (Mini Mental State Examination) and AQT (A Quick Test of cognitive speed). Postoperative delirium was assessed using Nursing Delirium Screening Scale (Nu-DESC) in which a score of ≥ 2 was considered as delirium. Results. Six patients (14%) scored high for postoperative delirium and all demonstrated impaired preoperative cerebrovascular reserve capacity. Median (25th – 75th percentile) BHI in patients with postoperative delirium was significantly lower compared to the non-delirium group (0.26 (-0.08 – 0.44) vs. 0.83 (0.57 – 1.08), p = 0.002). Preoperative MMSE score was lower in patients who developed postoperative delirium (median, 25th – 75th percentile; 26.5, 24 – 28 vs. 28.5, 27 – 29, p = 0.024). Similarly, patients with postoperative delirium also displayed a slower performance during the preoperative cognitive speed test AQT color and form (mean ± SD; 85.8 sec ± 19.3 vs. 69.6 sec ± 15.8, p = 0.043). Conclusion. The present findings suggest that an extended preoperative ultrasound protocol with TCD evaluation of cerebrovascular reserve capacity and neuropsychological tests may be valuable in identifying patients with increased risk of developing delirium after cardiac surgery.